Stratification Of LIver Disease (SOLID): protocol for a prospective observational cohort study to determine the optimum biomarker strategies for the detection of advanced liver disease at the primary–secondary care interface. Issue 1 (8th February 2023) - McPherson, Stuart; Jarvis, Helen; McGonigle, John; Bedlington, Joan; Dean, Jill; Hallsworth, Kate; Hanon, Elodie; Liddle, Trevor; Luvai, Ahai; Mansour, Dina; Patel, Preya; Renwick, Laura; et al.
Abstract : Introduction: Undiagnosed fatty liver disease is prevalent in the community, due to high rates of harmful alcohol consumption and/or obesity. Fatty liver disease can progress to cirrhosis and its complications. Early identification of liver disease and treatment may prevent progression to cirrhosis. Biomarkers including FIB-4, enhanced liver fibrosis (ELF), PRO-C3 and vibration controlled transient elastography (VCTE) can stage liver fibrosis, but it is not known how well they perform in a primary care population. Moreover, no assessment of long-term prognostic ability of these biomarkers has been conducted in primary care. We aim to evaluate the performance of fibrosis biomarkers in primary care to develop a pathway to detect advanced fibrosis. Methods and analysis: This prospective, observational cohort study will recruit 3000 individuals with fatty liver disease risk factors (obesity, type 2 diabetes or hazardous alcohol consumption) at their primary care 'annual chronic disease review'. Participants will have a 'liver health check'. Two pathways will be evaluated: (1) all have FIB-4, ELF and VCTE performed, and (2) patients have an initial assessment with FIB-4 and ELF, followed by VCTE in only those with increased FIB-4 and/or ELF. Individuals with suspected significant/advanced liver fibrosis (liver stiffness measurement>8 kPa), will be reviewed in secondary care to confirm their fibrosis stage and institute treatment. The performance of FIB-4, ELF, PRO-C3, VCTE and novel biomarkers alone or in combination for advanced fibrosis/cirrhosis will be evaluated. Participants will be followed longitudinally via their electronic health records to assess long-term clinical outcomes. Ethics and dissemination: Ethical approval was obtained from the London-Chelsea Research Ethics Committee (22/PR/0535; 27 June 2022). Recruitment began on 31 October 2022. Outcomes of this study will be published in peer-reviewed journals and presented at scientific meetings. A lay summary of the results will be available for study participants and will be disseminated widely by LIVErNORTH.